Rekonstruksi Keadilan Dalam Pembagian Harta Bersama Ketika Istri Lebih Dominan Mencari Nafkah: Perspektif Maqasid Syariah - Sugih Ayu Pratitis; Sukiati; Nurasiah; Mhd Yadi Harahap (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Changes in gender roles and the increasing economic participation of women in Indonesia have given rise to a new family reality in which wives often become the more dominant income earners. This condition raises issues of justice in the distribution of marital property after divorce, which has traditionally adhered to an equal division as stipulated in Article 97 of the Compilation of Islamic Law (KHI). This study aims to analyze the problem of justice in the distribution of marital property when the wife contributes more significantly to the household economy and to formulate a reconstruction of justice based on maqāṣid al-sharīʿah. This research employs a normative legal method with a descriptive-analytical approach, utilizing statutory, conceptual, comparative, and sociological approaches as supporting perspectives, with maqāṣid al-sharīʿah serving as the primary analytical framework. The data were obtained through a systematic literature review of primary, secondary, and tertiary legal materials and were analyzed qualitatively. The findings indicate that an equal division of marital property does not always reflect substantive justice when the economic contributions of husband and wife are unequal. The maqāṣid al-sharīʿah approach particularly the principles of hifẓ al-māl (protection of property) and hifẓ al-nasl (protection of family) emphasizes that justice should be understood proportionally, in accordance with the actual contributions of each party. Therefore, this study recommends a progressive interpretation of Article 97 of the KHI so that the distribution of marital property is more oriented toward public interest (maṣlaḥah) and substantive justice within Islamic family law in Indonesia